CAPAIAN PEMBELAJARAN LITERASI BERBASIS STEAM DI TK NEGERI PEMBINA TANJUNG BATU - Dea Suryani; Amir Hamzah; Lidia Oktamarina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the success of STEAM-based literacy learning at Pembina Tanjung Batu State Kindergarten. The STEAM-based literacy program for Science allows children to match words and pictures of the moon, Technology allows children to name the months through storytelling, Engineering allows children to cut out moon patterns to make posters, Art allows children to name the months and stick them on cardboard, and Mathematics allows children to calculate moon patterns. The STEAM-based literacy learning program at Pembina Tanjung Batu State Kindergarten has been running well, with the STEAM-based literacy learning program planning from planning to implementation to evaluation. The objectives were to determine the planning of STEAM-based literacy learning at Pembina Tanjung Batu State Kindergarten, to determine the implementation of STEAM-based literacy learning at Pembina Tanjung Batu State Kindergarten, and to determine the evaluation of STEAM-based literacy learning at Pembina Tanjung Batu State Kindergarten. This research used a qualitative research approach with a case study approach. The subjects of this study focused on children aged 5-6 years. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used data triangulation, namely: data reduction, data presentation, conclusion drawing, and verification. The results of this study indicate that STEAM-based literacy learning at Pembina Tanjung Batu State Kindergarten has been running well, as demonstrated by the program's implementation. This includes planning teaching modules that include objectives, learning outcomes, indicators, and supporting learning activities, as well as implementation and evaluation. This has resulted in optimal STEAM-based literacy for children at Pembina Tanjung Batu State Kindergarten